Contribuições no diagnóstico e no tratamento cirúrgico de cães com doença do disco intervertebral cervical - Schwab, Marcelo Luís (2019)
To identify compression in the spinal cord of dogs with cervical intervertebral disc disease (DDIV) it is necessary to use advanced imaging tests such as myelography. However, in this segment, little is known about the importance and necessity of performing different myelographic views, which are already well established for the thoracolumbar region. In addition, when lateral compression is identified in the exam, surgical decompression by the hemilaminectomy technique is indicated. However, no studies were found demonstrating the inefficacy of the ventral slot technique in these cases. Thus, the aims of this study was to verify in which of the myelographic views was possible to identify spinal cord compression in dogs with cervical intervertebral disc disease (IVDD), to establish a sequence in which myelographic views should be obtained for this region and to verify the clinical recovery of dogs submitted to ventral slot surgical decompression in lateralized compressions of the cervical spinal cord caused by intervertebral disc disease (IVDD). For the first study four myelographic views (lateral, ventrodorsal, left oblique and right oblique) of 41 patients diagnosed with cervical IVDD were evaluated. In 40 patients (97.5%) it was possible to identify spinal cord compression by lateral view, 22 (53.6%) by the oblique view, and 11 (26.8%) by the ventrodorsal view (p<0.0001). There were lateralized compressions in 22 (53.6%) patients, detected by all oblique views (100%) and by 11 (50%) of the ventrodorsal views. In 10 (24,4%) dogs, it was observed more than one compression site, which ventrodorsal view helped to decide the site in 50% of the cases and oblique in 70%. For the second study twenty patients were selected in different degrees of neurological dysfunction with definitive diagnosis of lateralized compression by cervical IVDD. Postoperative clinical recovery was assessed in patients who had undergone at least two months of the surgical procedure. There was a satisfactory recovery in 19 dogs (95%) and unsatisfactory recovery in another (5%), showing a significant clinical improvement (p <0.05) in the use of this technique in lateralized compression cases. From this it can be concluded that all the tested myelographic views allow the identification of spinal cord compressions in dogs with cervical IVDD, the lateral view being the most relevant, followed by the oblique and ventrodorsal view, therefore establishing a sequence of myelographic views should be obtained for this region; and that the ventral slot promotes satisfactory clinical recovery of dogs with lateralized compression of the spinal cord caused by cervical.